73 Elderly Patients do not appear to be at Increased Risk of Pacemaker and Complex Device Related Complications. (6th June 2015) - Brown, Louise; Fox, Lauren; Luck, Hazel; Stewart, Michael; Farrell, Tom; Kalra, Paul; Andrews, Neil; Morton, Geraint; Hobson, Alex
Abstract : Introduction: Pacemaker and complex device implantation is becoming increasingly common as indications expand and are better recognised. As the population ages, increasingly complex procedures are performed in district general hospitals in older, frailer patients. Historic benchmark pacing studies included younger patients and underestimate contemporary rates of device related complications. We reviewed complication rates across all pacing procedures in a high-volume district general hospital and compared rates across age ranges. Methods: All pacing procedures between January 2013 and April 2014 were retrospectively identified from the NICOR database. Procedural reports and pacing checks for all new implants, lead revisions, generator changes and system upgrades for all implantable device types were reviewed. Complications were recorded and classified as major or minor (Table 1 ). Complication rates were compared across age ranges, by sex and procedural priority. Results: 775 procedures were reviewed. The overall complication rate was 10.7%. This comprised of a rate of 8.4% for major complications vs.2.3% for minor complications. 356 (46%) of patients were >80. Complication rates were not influenced by patient age (p = 0.8), sex (p = 0.1) or procedural priority (p = 0.6) (Table 2 ). A trend was seen for increasing complication rate corresponding to the complexity of the device and number of leads implanted (Figure 1 ). Lead displacement was the commonest complication although re-intervention did not translate into a high rate of infection or wound problems as all other complications occurred with a frequency of < 1%. Within brady-pacing, 87.5% of right ventricular leads used passive fixation. The rate of lead displacement was higher in the passive ventricular leads (5.2%) as compared to the active ventricular leads (3.8%) however this did not reach not statistical significance (p = 0.68). The rate of lead displacement did not vary significantly between the age groups (p = 0.44). Conclusions: Complication rates from implantable cardiac device procedures were not insignificant but are comparable in a high volume district hospital to other contemporary data. Older patients made up a high proportion of patients undergoing pacing procedures but did not have a higher complication rate. The major complication was lead displacement and there was a corresponding increase in complications with increasing complexity of the device and the number of leads implanted.